2022
DOI: 10.7759/cureus.31985
|View full text |Cite
|
Sign up to set email alerts
|

Can a Cerebral Congenital Anomaly Present in Adulthood?

Abstract: Colpocephaly, a congenital anomaly in the ventricles, is usually discovered early in infancy and rarely during adulthood. Partial or complete agenesis of the corpus callosum or Chiari malformations (developmental arrest of white matter formation in early fetal development) can lead to abnormal asymmetrical ventricular enlargement. Minimal literature about colpocephaly is available for clinicians, making diagnosis and treatment very challenging. Colpocephaly in adults is an infrequent condition, mostly found as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Review of current literature suggests colpocephaly is often an incidental diagnosis in adults. Adult patients usually present with nonspecific symptoms such as headache [1 , 2 , 3 , 10] , dizziness [2 , 6] , seizures [6 , 11] , vertigo [1] , nausea [6] , motor abnormalities [16] , sensory abnormalities [12] , cognitive abnormalities [15 , 17] , intellectual disability [18] , learning disability [17] , gait instability and falls [9] , loss of consciousness [13] and visual hallucinations [19] . Gungor et al reported a case with postmortem diagnosis of colpocephaly in a patient with a lifelong history of poor academic performance [20] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Review of current literature suggests colpocephaly is often an incidental diagnosis in adults. Adult patients usually present with nonspecific symptoms such as headache [1 , 2 , 3 , 10] , dizziness [2 , 6] , seizures [6 , 11] , vertigo [1] , nausea [6] , motor abnormalities [16] , sensory abnormalities [12] , cognitive abnormalities [15 , 17] , intellectual disability [18] , learning disability [17] , gait instability and falls [9] , loss of consciousness [13] and visual hallucinations [19] . Gungor et al reported a case with postmortem diagnosis of colpocephaly in a patient with a lifelong history of poor academic performance [20] .…”
Section: Discussionmentioning
confidence: 99%
“…Asymptomatic adults in whom colpocephaly is diagnosed incidentally usually require no treatment [3 , 11] . For symptomatic adult patients, management is symptomatic: the most common example being antiepileptics for patients presenting with seizures [11 , 12 , 19] . Our patient was prescribed antiepileptics due to the symptoms reported by her family as well as abnormal EEG findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pott's puffy tumor is osteomyelitis of the skull bones, leading to forehead swelling. It occurs most commonly secondary to the direct spread of bacterial infection from the surrounding tissues, such as the nasal cavity, sinuses, or oral cavity [ 13 ]. Angular cheilitis, a common, non-contagious, inflammatory condition affecting the corners of the mouth or oral commissures can also develop in IBD or other conditions such as eczema, vitamin B deficiency, or excessive saliva.…”
Section: Discussionmentioning
confidence: 99%